Does faith has impact on investment return: evidence from REITs - Zhang, Weiwei; Sun, Tiezhu; Wang, Zilong; Kumar, Vishnu Raj; Ma, Yechi (International Journal of Strategic Property Management, 2019)
This paper investigates whether faith has impact on investment returns. Specifically, we choose the Shariah compliance and REITs investment for the purpose of investigation. Synthetic Shariah compliant portfolios are constructed with various interpretation of compliance. We compare the performance of Shariah compliant portfolios with US Equity REIT portfolio during 1993–2017 by examining the abnormal returns using CAPM and Carhart four-factor model. We find no evidence of underperformance or outperformance of the Shariah compliant investments. This is also true during the financial crisis periods which is confirmed by the sub-sample analysis. Our findings suggest that Shariah compliant REIT investor faces no cost or gain in his investments as a result of his faith.